Long-term efficacy and safety of netakimab in patients with moderate-to-severe psoriasis. Results of phase II open-label extension clinical study BCD-085-2-ext - A. L. Bakulev; A. V. Samtsov; A. A. Kubanov; V. R. Khairutdinov; M. M. Kokhan; A. V. Artemyeva; S. I. Derbin; E. V. Chernyaeva; R. A. Ivanov (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Netakimabis original monoclonal antibody against IL-17. This article outlines the key results of a phase II open-label extension trial of netakimab 80 mg and 120 mg in patients with moderate-to-severe psoriasis.The main aim of the trial is to estimate efficacy, safety and immunogenicity of long-term treatment with netakimab 80 mg and 120 mg in patients with moderate-to-severe psoriasis.Materials and methods. The BCD-085-2-ext study is a comparative, open-label phase 2 clinical study of the effi - cacy and safety of netakimab in patients with moderate-to-severe plaque psoriasis who had finished BCD-085-2 (NCT02762994) trial. Main efficacy endpoints includePASI75, PASI90, PASI100, sPGA = 0-1 on week 38 of the trial, long-term PASI75/90/100 retention, efficacy keeping after switch from once every 2 week regimen to once every 4 week regimen. Safety endpoints include adverse events, serious adverse events number and their profile.Results. 103 patients were included. PASI75 at week 38 was reached by 98.06 %, PASI90 - by 92.23 %, PASI100 - by 59.22 % of patients. There were no cases of serious adverse event, early with drawal due to adverse events and cases of grade 4 toxicity according to CTCAE 4.03. There were no cases of binding antibodies to netakimab during the 38 weeks of the study.Conclusion. The first Russian original IL-17 inhibitor netakimabis promising modern medicine for moderate-to-severe plaque psoriasis treatment. Netakimabshowed high efficacy, favorable safety profile and low immunogenicity during one year of the treatment.